EFEKTIVITAS PEMBELAJARAN PROBLEM BASED LEARNING DENGAN ZOOM MEETING DI SDN KEBRAON II - Hadi Prayitno, Sunyoto (Pendidikan Dasar - Pascasarjana Universitas Negeri Jakarta, 2021)
Abstract: Teachers and students need the right media and appropriate learning during the COVID-19 pandemic. The target of achieving learning outcomes is the goal. This goal requires students to have critical thinking skills. By applying the problem-based learning model and the right media as well as the zoom meeting application to make it easier for teachers and students in teaching and learning activities. This research to know the effectiveness of problem-based learning by applying zoom meeting in class V of SDN Kebraon II is a descriptive quantitative study. The subjects used were fifth-grade students of SDN Kebraon II. Data were obtained using 4 instruments, namely: learning management observation sheets and student activity observations, learning outcomes test questions, and student response questionnaire sheets. Then the data were analyzed descriptively according to the indicators of each aspect, namely learning management, student activities, and learning outcomes, as well as student responses. The research results on the observation aspect of learning management have a value of 3.64 which is included in the